Quantification of Circulating Activated Protein C in Human Plasma by Immunoassays - Enzyme Levels are Proportional to Total Protein C Levels - España, Francisco; Zuazu, Isabel; Vicente, Vicente; Estellés, Amparo; Marco, Pascual; Aznar, Justo (Thrombosis and Haemostasis, 1996)
We have developed a simple assay that measures the circulating activated protein C (APC) in plasma. The assay requires collection of duplicate blood samples, one in citrate plus heparin and the other in citrate plus inhibitors of the enzyme. In the heparin tube, APC reacts completely and irreversibly with its major plasma inhibitors, protein C inhibitor (PCI) and α1-antitrypsin (α1AT), and the complexes formed are measured by ELISAs. The amount of circulating APC is calculated from the difference between the total amount of complexed APC (sample in citrate plus heparin) and the amount of APC complexed in vivo (sample in citrate plus inhibitor). Over 95% of the APC added to blood collected with heparin was recovered in the assay. The assay can easily be performed in four hours, and had a detection limit of 0.1 ng/ml APC. The mean APC level in 18 protein C heterozygous members from seven kindreds was significantly lower (0.6 ± 0.3 ng/ml) than in 20 healthy controls (1.1 ± 0.3 ng/ml) (p <0.001), whereas the mean level in 10 non-affected members from the kindreds studied was 1.5 ± 0.3 ng/ml. In the group of 12 nonanticoagulated heterozygous protein C-deficient individuals, the three patients with a history of venous thrombosis had a mean APC level significantly lower than the nine asymptomatic members (p <0.01), both subgroups showing similar protein C levels. There was a significant correlation in all groups between the levels of APC and the levels of protein C antigen (r = 0.758, p <0.0001) and activity (r = 0.745, p <0.0001), which means that APC circulating levels are proportional to protein C levels and suggests that the protein C level is the limiting factor in the rate of protein C activation in vivo.